2010
DOI: 10.5897/ajb10.984
|View full text |Cite
|
Sign up to set email alerts
|

Induction of phenolics, lignin and key defense enzymes in eggplant (Solanum melongena L.) roots in response to elicitors

Abstract: Elicitors are capable of mimicking the perception of a pathogen by a plant, thereby triggering induction of a sophisticated defense response in plants. In this study, we investigated an induced resistance in eggplant in respect to cell wall strengthening and defense enzyme activation affected by four elicitors such as, chitosan (CHT), salicylic acid (SA), methyl salicylate (MeSA) and methyl jasmonate (MeJA). The increase in total phenolic content of eggplant roots by the elicitors was significantly higher. Lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(11 citation statements)
references
References 56 publications
0
8
1
2
Order By: Relevance
“…However, after 12h of exposure there was no signifi cant difference in phenolic compound content between the treatment and the control (1657µg of phenic acid g FM -1 ) ( Figure 1C). These results are somewhat different to those of a recent study in Solanum melongena L. using different types of elicitors and different exposure times (MANDAL, 2010). The previous showed that salicylic acid was the most effi cient elicitor at triggering phenolic compound synthesis after 48h exposurealthough a gradual decrease in synthesis was observed over longer time periods (MANDAL, 2010).…”
Section: Resultscontrasting
confidence: 56%
“…However, after 12h of exposure there was no signifi cant difference in phenolic compound content between the treatment and the control (1657µg of phenic acid g FM -1 ) ( Figure 1C). These results are somewhat different to those of a recent study in Solanum melongena L. using different types of elicitors and different exposure times (MANDAL, 2010). The previous showed that salicylic acid was the most effi cient elicitor at triggering phenolic compound synthesis after 48h exposurealthough a gradual decrease in synthesis was observed over longer time periods (MANDAL, 2010).…”
Section: Resultscontrasting
confidence: 56%
“…Gibberellin also significantly increased the sprouts' lengths. According to results reported in the literature, healthy plants respond to exogenous MeJA by activating their defense responses (Mandal, 2010;Xiao et al, 2009). MeJA may stimulate gene expression and enzyme activity related to the synthesis of some secondary metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the level of salicylic acid (SA) increased after apoplastic H 2 O 2 bursts mediated by NADPH oxidases and extracellular peroxidases (O'Brien et al, 2012; Mammarella et al, 2015), though in this case a biosynthesis route involving ICS was implicated (Herrera-Vásquez et al, 2015), however, we did not see ICS induction at any time point examined, but cannot rule out its participation in the flax response. In consequence, SA and/or its methylated form—MeSA would lead to the induction of lignin biosynthesis as PAL-dependent lignification was shown to be induced by SA and MeSA (He and Wolyn, 2005; Mandal, 2010), which is involved in plant defense signaling (Park et al, 2007), leading to SAR and among other things to induction of lignin formation (Mandal, 2010). A simplified scheme of the phenylpropanoid pathway with marked changes in the metabolite contents and transcript levels is presented in Figure 2.…”
Section: Discussionmentioning
confidence: 99%